The Inauguration of Asian Pacific Journal of Cancer Biology - Mosavi Jarrahi, Alireza (Asian Pacific Journal of Cancer Biology, 2016)
On behalf of the Asian Pacific Organization for Cancer Prevention (APOCP) and its subsidiary (the West Asia Organization for Cancer Prevention- WAOCP), it is a great honor to present the inaugural issue of Asian Pacific Journal of Cancer Biology (APJCB, ISSN ). APJCB is branching out from Asian pacific Journal of Cancer Prevention to become the journal of choice for the large community researchers in the Asian and Pacific region who work on the biology of cancer. Its goal is to become leading online forum to disseminate the work of Asia and Pacific Regions’s cancer scientists to the global audience. APJCB inherits its inception from the backbone of 17 years of successful publication of the Asian Pacific Cancer Prevention (APJCP) and considers itself as a sister publication of the APJCP.